Factors associated with cognitive function in older adults in Mexico - Jenny Miu; Joel Negin; Aarón Salinas-Rodriguez; Betty Manrique-Espinoza; Ana Luisa Sosa-Ortiz; Robert Cumming; Paul Kowal (Taylor & Francis Group, 2016)
Background: As populations age, cognitive decline and dementia pose significant burdens for societies and health care systems, including low- and middle-income countries such as Mexico. Minor age-related declines in cognitive function appear to represent a stable but heterogeneous phase in the continuum between normal cognitive ageing and dementia. Loss of cognitive function has impacts at societal and individual levels and understanding the risk factors can help provide a framework for health policies and interventions to target at-risk groups. Design: A cohort of older Mexican adults (50+) from the World Health Organization's Study on global AGEing and adult health (WHO SAGE) was used to examine cognitive function, including a total of 2315 respondents, with 325 respondents aged 80 years and older. Cognition was objectively evaluated using verbal recall, verbal fluency, forward digit span and backward digit span, with differences in an overall cognitive score assessed against sociodemographic variables, and associated factors using linear regression. Results: The most significant predictors of poorer cognitive function were found to be older age (β=−13.88), rural living (β=−2.25), low income (β=−8.28), self-reported severe or extreme memory difficulties (β=−6.62), and difficulty with two or more activities of daily living (β=−2.02). Conclusions: These findings can inform public health initiatives to address cognitive impairment in ageing populations in Mexico and other middle-income countries.